A Fermi Accelerator Model - Leonel, Edson Denis [UNESP] (My University, 2021)
In the earlier chapter we discussed the concepts of two dimensional mappings. This chapter is dedicated to the investigation of the Fermi accelerator model, also called as Fermi-Ulam model, which is made via a two-dimensional mapping. We discuss how to construct the equations governing the dynamics of the model, the main properties of the phase space including an investigation of the fixed points stability and show that the chaotic sea admits a scaling invariance property.